«A suitable successor»: Building Legitimacy in Hilary’s Sermon on the Life of Honoratus - Natal, David (Reti Medievali Rivista, 2015)
The monastic and hagiographical contents of Hilary’s Sermon on the Life of Honoratus (430-431) have received substantial consideration. Much less attention has been paid to the role the sermon played in the specific context of Arles. In this article, I will focus attention on the social and political dimension of the text and will argue that Hilary’s main purpose was to justify his election as bishop of Arles. Hilary portrayed Honoratus as the ideal bishop and exploited the similarities between the two in order to present himself as the suitable successor.